Current challenges and future directions in data assimilation and reanalysis - Valmassoi, Arianna (2023)
The first Joint WCRP1-WWRP2 Symposium on Data Assimilation and Reanalysis took place on13-17 September 2021, and it was organized in conjunction with the ECMWF Annual Seminaron observations. The last WCRP/WWRP-organized meetings were held separately for data assimilation and reanalysis in 2017 (Buizza et al. 2018; Cardinali et al. 2019). Since then, commonchallenges and new emerging topics have increased the need to bring these communities together toexchange new ideas and findings. Thus, a symposium involving the aforementioned communitieswas jointly organized by DWD3, HErZ4, WCRP, WWRP, and the ECMWF annual seminar. Majorgoals were to increase diversity, provide early career scientists with opportunities to present theirwork and extend their professional network, and bridge gaps between the various communities.The online format allowed more than 500 participants from over 50 countries to meet in avirtual setting, using the gathertown 5 platform as the central tool to access the meeting. A virtualconference center was created where people could freely move around and talk to other close-byparticipants. A lobby served as the main hub and it connected the poster halls and the conferencerooms for the oral presentations and the ECMWF seminar talks. The feedback from the participantswas overwhelmingly positive.Scientifically, the meeting offered opportunities to bring together the communities of Earth systemdata assimilation, reanalysis and observations to identify current challenges, seek opportunitiesfor collaboration, and strategic planning on more integrated systems for the longer term. Thecontributions totalled 140 oral and over 150 poster presentations covering a large variety oftopics with increased interest in Earth system approaches, machine learning and increased spatial resolutions. Key findings of the symposium and the ECMWF annual seminar are summarized insection 2. Section 3 highlights the common and emerging challenges of these communities.